Impact of Zirconia and Lanthanum Promoters on Multiwalled CNT Generation in Dry Reforming of Methane - Manan, Wan Nabilah; Wan Isahak, Wan Nor Roslam; Yaakob, Zahira; Samidin, Salma (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
In this study, three distinct carbon nanotubes (CNTs) — Zr-Ni/CeO2, La-Ni/CeO2, and Ni/CeO2 were produced via dry reforming of methane (DRM) at 800°C for 180 minutes. These catalysts were initially synthesized using ultrasonic-assisted citric impregnation method to enhance metal promoter dispersion. X-ray diffraction (XRD) confirmed that Zr and La doping minimized carbon deposition. Brunauer-Emmett-Teller (BET) analysis revealed typical mesoporous structures of stacked laminar nanorods. Thermogravimetric analysis (TGA) quantified carbon deposits as Zr-Ni/CeO2 (5.1 wt%) < La-Ni/CeO2 (7.85 wt%) < Ni/CeO2 (11.3 wt%). TEM and FESEM confirmed the formation of multiwalled carbon nanotubes (MWCNTs), while XPS provided insights into surface chemistry, oxidation states, and defect sites. Doping with Zr and La enhanced crystallinity, CeZr phase formation, thermal stability, and reduced carbon deposition, with MWCNTs exhibiting higher graphitization (IG/ID: Zr-Ni/CeO2 = 1.25, La-Ni/CeO2 = 1.59) compared to Ni/CeO2 (IG/ID = 1.15). This discovery represents a breakthrough in catalyst development, providing a dual advantage of reducing carbon deposition and boosting H₂ production in the Dry Reforming of Methane (DRM) process. The carbon formed is primarily multi-walled carbon nanotubes (MWCNTs), which not only minimize harmful carbon accumulation but also enhance overall catalytic performance. This innovation offers a sustainable solution for carbon management and the conversion of greenhouse gases. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).